Climate Change Will Re-draw the Map for Marine Megafauna and the People Who Depend on Them - Grose, Susan O.; Pendleton, Linwood; Leathers, Amanda; Cornish, Andrew; Waitai, Sheridan (Frontiers in Marine Science, 2020)
Climate change is expected to dramatically alter the distribution of many marine megafauna, impacting the people and economies that depend upon them. We build upon the recent literature by developing a framework to describe the effects these changes will have on marine megafauna. With the goal to assist policy makers and grass roots organizers, we identify three illustrative pathways by which climate change drives these range shifts: 1) effects on habitat and shelter, 2) impacts on reproduction and disease, and 3) changing distribution of sources of food. We examine non-climate factors that may constrain or enable megafauna to adapt, creating winners and losers both for the species and the people dependent upon them. Finally, we comment on what management strategies exist at international and local scales that could help mitigate these impacts of climate change so that we, as a global community, can ensure that marine megafauna and people can best co-exist in a changing world.